Improved propagation, maximizing yield and enhancing zerumbone production in Zingiber zerumbet (L.) Smith. through shading and NPK fertilization - Goh, Suzanne (2019)
Previous studies on Zingiber zerumbet focused mainly on chemical and biological properties of rhizome extract resulting in lack of information on cultivation practices and problems on rhizome dormancy. The determination of shade level and nitrogen (N), phosphorus (P), potassium (K) fertilizer rates are imperative for improvement on growth and rhizome yield of this high medicinal value plant. In addition to having various pharmacological traits, the species are said to be associated with a predominant compound, zerumbone (ZERU), justifying enhancement initiatives on ZERU in the species. The objectives of the present study include improvement in propagation by breaking rhizome dormancy, determination of optimum shade level and maximizing yield through NPK fertilization. The study also aimed at evaluating the inhibition effect on cytotoxic mediators of ZERU in activated microglial cells. At 100 mg/L, 6-Benzylaminopurine (BAP) and ethephon (300 mg/L) performed better in promoting breaking of dormancy in term of highest percentage of bud sprouted. Three shade levels (full sun, 30% and 50% shade levels) and five combinations of NPK fertilizer rates were tested in plant growth and yield performance. Increasing shade level and NPK fertilizer rates showed promoting pattern in plant height, number of leaves, total leaf area per plant, rhizome fresh and dry weight. Field experiment showed that 50% shade with NPK 4 (120 kg N/ha/yr, 140 kg P/ha/yr and 230 kg K/ha/yr) is the best cultural practice with highest rhizome yield (29.71 tonne per hectare) at 10 months after planting (MAP). Production of ZERU as affected by shade level and NPK fertilizer rates was evaluated using High Performance Liquid Chromatography (HPLC) with validated method. The highest concentration of ZERU (40.85% dw/dw) was from plants in pot trial grown under 50% shade and treated with NPK 3 (90 kg N/ha/yr, 105 kg P/ha/yr and 172 kg K/ha/yr). In the field experiment, ZERU decreased with increasing MAP. The highest ZERU content was found in plants harvested at 6 MAP treated with Chicken Manure and NPK 3 (90 kg/ha/yr of N, 105 kg/ha/yr of P and 172 kg/ha/yr of K) at 34.10 % (dw/dw) and 33.04 % (dw/dw) respectively. The rhizome extracts from pot trial and ZERU were used to treat BV2-murine microglial cells with stimulation by lipopolysaccharide (LPS).The results showed selected rhizome extracts and ZERU were significantly reduced nitric oxide (NO) and reactive oxygen species (ROS) level in LPS-stimulated BV2 cells. These results showed that propagation of Zingiber zerumbet can be improved by application of BAP at 100 mg/L and ethephon at 300 mg/L while the yield and quality of rhizome was controlled by shading and NPK fertilization. The preliminary study on neuroinflammation showed that ZERU and extracts of rhizome has anti-inflammatory and anti-oxidant properties with significant reduction of NO level and ROS level.